Developing Interactive Multimedia, Material Rule of Simple Past Tense Early Childhood Education Programs STKIP Kumala Metro Lampung - Purwo Trapsilo (State Institute for Islamic Studies IAIN of Metro, 2018)
The aims of the research are: (1) to describe the condition and potency of current learning on the basic material Simple Past tense, (2) to produce teaching learning materials Compact Disc (CD) interactive multimedia which is integrated with basic competence in the form of procedural text with manuals and tips, (3) to analyze the effectiveness, (4) to find efficiency, and (5) to find attractiveness of the program.The method of the research used research and development and it was conducted at one semester students STKIP KUMALA Data were collected through observation, questionnaires and tests. Analyze data uses descriptive and Gain test. The conclusions of research are; (1) STKIP KUMALA has the potency of using IT, tools and infrastructure of computer, teaching material to support the teaching process, (2) the process produced the product through lector program, (3) The teaching and learning process utilizing interactive multimedia teaching material is more effective, shown by N-Gain score 0.71, (4) after using interactive multimedia, the teaching and learning process can save 90 minutes compared to the previous lesson, (5) learning using interactive multimedia interesting, in organizing strategy (87.00%), in terms of delivery (84,97%), and in terms of program management strategies to obtain optimal learning results (85.04%).